Improving Students' Understanding of Disaster Mitigation Through Problem-Based Learning (PBL) - Putri, Wa; Lasaiba, Mohammad Amin; Leuwol, Ferdinad Salomo (GEOFORUM, 2024)
This research aims to improve students' understanding of disaster mitigation through the Problem-Based Learning (PBL) approach. PBL is a student-centered learning method, in which they are actively involved in solving real problems, in this case, natural disasters. The implementation of PBL in the context of disaster mitigation is expected to increase students' awareness and readiness to face potential disasters in their environment. The research was conducted with a descriptive quantitative approach, involving high school students living in disaster-prone areas. The results showed that the implementation of PBL significantly improved students' understanding of disaster mitigation measures, such as risk identification, evacuation planning, and self-rescue. In addition, students also demonstrate improved skills in working collaboratively to solve complex problems. Through group discussions and disaster simulations, students are better able to apply theory into real practice. These findings show that PBL is an effective method in disaster mitigation education, because it is able to integrate problem-based learning with practical experience. Thus, PBL can be a widely adopted learning strategy to increase the readiness of the younger generation to face future disaster threats.